Testing for the Fisher Hypothesis under Regime Shifts in Turkey: New Evidence from Time-Varying Parameters - Arısoy, Ibrahim (International Journal of Economics and Financial Issues, 2013)
This paper examines the validity of Fisher hypothesis in Turkey for the time period 1987Q1-2010Q3. For this purpose, we employ cointegration test with a structural break as well as time varying parameters approach (TVP) that takes into account the effects of regime or policy changes on the relation between interest rate and inflation rate. The empirical results show that weak form of the Fisher hypothesis holds in Turkish economy. Keywords: Fisher Effect; Cointegration; Regime Shift; Time-Varying Parameters; Kalman Filter JEL Classifications: C12; E40; E50